Hybrid cascaded multilevel converter with integrated series Active Power Filter for interfacing energy storage system to medium voltage grid - Rashed, Mohamed; Klumpner, Christian; Asher, Greg (2010)
This paper presents a new control strategy for a high performance hybrid cascaded H-Bridge HB multilevel converter with integrated series Active Power Filter Stage APFS. Unequal DC voltage sources are used to energise the converter's HBs. This offers increased number of voltage levels using fewer number of series connected HBs. Simple hybrid stair-case/SVM modulation strategy is proposed to synthesise the converter output voltage waveforms and to guarantee even sharing of power between the converter's HBs. Novel capacitor voltage balancing controller is proposed and designed to guarantee decouple control of the APFS active power during the capacitors' charging and discharging modes without compromising the quality of the converter output voltage. The proposed converter is investigated under different operating conditions and the results show excellent dynamic and steady state performance.